Little bear's visit eaudiobook - Holmelund Minarik, Else (Weston Woods, 1967)
"An endearing story filled with tenderness, humor, and warm family relationships." (Booklist) Little Bear likes to visit Grandmother and Grandfather Bear. He likes to try on Grandfather's hat. He likes Grandmother's cooking. But best of all, he loves the stories his grandparents tell him, of robins and goblins, and of Mother Bear when she was little.A beloved classic from Else Holmelund Minarik and Maurice Sendak.In the Little Bear stories, we meet Little Bear, whose adventures are filled with humor and joy. And we meet Mother Bear, who is there whenever Little Bear needs her. When it is cold and snowy outside, she finds just the right outfit for Little Bear to play in. When he goes to the moon, she has a hot lunch waiting for him on his return. And, of course, she never forgets his birthday.